The CONCEPTION of AL-QUR’AN on EDUCATOR; Study of QS. Ali Imran : 79 - Sahan Sahan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
This article studies the conception of al-Qur’an, sura Ali Imran verse 79. The result of my study shows that a teacher should have rabbani values. The indicators of these values are: first, a teacher must follow and obey loyally to God . Second, a teacher should complete rabbaniyah characteristic with sincerity. Third, a teacher should teach his students patiently. Fourth, when a teacher transfers his knowledge to his students, he should have honesty. Fifth, a teacher should improve his insight, knowledge and study. Sixth, a teacher should be able to create method of teaching. Eleventh, a teacher should be firm and put everything in a proper way so that he can control his students. Eighth, a teacher is demanded to understand psychological aspects related to his learners such as child psychology, development psychology, and education psychology. Ninth, a teacher is demanded to be responsive related to the society’s demand and life’s phenomena. Tenth, a teacher is demanded to be fair to all of his students.